2013
DOI: 10.1080/17458080.2013.794309
|View full text |Cite
|
Sign up to set email alerts
|

Quantum confinement effect on trilayer graphene nanoribbon carrier concentration

Abstract: In this study, one-dimensional vision of carrier movement based on the band structure of trilayer graphene nanoribbon in the presence of a perpendicular electric field is employed. An analytical model of ABA-stacked trilayer graphene nanoribbon carrier statistics as a fundamental parameter of field effect transistor (FET) in corporation with a numerical solution is presented in the degenerate and non-degenerate limits. The simulated results based on the presented model indicate that the model can be approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The comparison study between the presented model with data from [62,64] showed that due to the quantum confinement effect [39,43], the value of the subthreshold slope in the case of TGN SB FET is less than those of DG metal oxide semiconductor and vertical silicon-on-nothing FETs [62,64] for some values of drain-source voltage. A nanoelectronic device characterized by a steep subthreshold slope displays a faster transient between on-off states.…”
Section: Resultsmentioning
confidence: 99%
“…The comparison study between the presented model with data from [62,64] showed that due to the quantum confinement effect [39,43], the value of the subthreshold slope in the case of TGN SB FET is less than those of DG metal oxide semiconductor and vertical silicon-on-nothing FETs [62,64] for some values of drain-source voltage. A nanoelectronic device characterized by a steep subthreshold slope displays a faster transient between on-off states.…”
Section: Resultsmentioning
confidence: 99%
“…In this method, a self-consistent Hartree approximation can be utilized to estimate the induced charges on the different layers of BGN. This is because, as the Fermi surface of the intrinsic BGN communicates to the K-points, the tightbinding method is a suitable technique for the low energy excitations [23]. In addition, the tight-binding method with a single orbital per atom includes coupling parameters between the neighbor sites within BGN layers.…”
Section: Proposed Modelmentioning
confidence: 99%
“…In fact, the orbitals are considered to study the behavior of electrons around the Fermi level. The different sp 2 orbitals that are lower than the orbital in energy will have much more overlap with the orbitals of the same symmetry on adjacent atoms [23]. Furthermore, the interaction between the orbitals of adjacent atoms is small, which results in bonding and antibonding orbitals close to the Fermi level.…”
Section: Proposed Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This delicate difference in stacking order leads to an exhibitive distinction in band structure and transport features. At the Dirac point, B-TGN becomes metallic, whereas r-TGN remains insulating with an inherent interaction-driven gap of 6 meV [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In fact, ABA-stacked TGN shows semi-metallic behaviour with a tunable band overlap; however, ABC-stacked TGN with a tunable band gap is known as a semiconductor which is selected for the proposed sensor.…”
Section: Introductionmentioning
confidence: 99%